The national trial and trial production of two quality rice lines VH1 and VH2 obtained by haploid selection-anther culture method - Van, Nghiem Nhu; Loi, Cao Thi; Binh, Le Tran (Academia Journal of Biology, 2014)
The two quality rice lines VH1 (Vuhuong) and VH2, which were obtained by anther culture method in previous works, were selected for the national trial and trial production. Beside good eating and multi-resistance characteristics, they also showed equivalence in yield to control varietes. Up to present, the planting area of them has reached about 2 hectares.